Odpowiedź :
p = 1/2 e*f
96 = 12*f/2
96 = 6f | :6
f = 16
16/2 = 8
a²+b² = c²
8²+3²=c²
64+9=c²
73 = c² | √
c = √73
96 = 12*f/2
96 = 6f | :6
f = 16
16/2 = 8
a²+b² = c²
8²+3²=c²
64+9=c²
73 = c² | √
c = √73
P = 96
P = e*f/2
e = 12
f= ?
96=(12*f)/2 |*2
12*f=192
f=192/12
f=16 (druga przekątna)
I teraz z twierdzenia Pitagorasa
a²+b²=c²
a=1/2e
a=1/2*12=6
b=1/2f
b=1/2*16=8
6²+8²=c²
c²=36+64
c²=100
c=√100
c=10
Bok rombu jest równy 10.
P = e*f/2
e = 12
f= ?
96=(12*f)/2 |*2
12*f=192
f=192/12
f=16 (druga przekątna)
I teraz z twierdzenia Pitagorasa
a²+b²=c²
a=1/2e
a=1/2*12=6
b=1/2f
b=1/2*16=8
6²+8²=c²
c²=36+64
c²=100
c=√100
c=10
Bok rombu jest równy 10.
P=d₁ x d₂ : 2
96= 12 x d₂ : 2
96= 6 x d₂
d₂=96 : 6
d₂= 16
spr.
P=12 x 16 : 2
P= 192 : 2
P= 96
96= 12 x d₂ : 2
96= 6 x d₂
d₂=96 : 6
d₂= 16
spr.
P=12 x 16 : 2
P= 192 : 2
P= 96